(untitled) (Bibliouniversitas@ABRM.md, 2025)
This paper explores the impact of Artificial Intelligence on social networks, examining both the opportunities and challenges it presents. It reflects on how AI can enhance user interactions and the services offered by libraries on social media. The benefits and role of Artificial Intelligence in identifying and mitigating the spread of fake news and misinformation on social media are argued, highlighting content that appears suspicious and helping platforms to act swiftly to prevent the dissemination of false information. AI involves striking a balance between innovation and ethics. The article discusses the results obtained regarding the use and effectiveness of social media by the Scientific Library of USARB to communicate and interact with its users.